Leaching Efficacy of Ethylenediaminetetraacetic Acid (EDTA) to Extract Rare-Earth Elements from Monazite Concentrate - Ammar S. A. Al Sheidi; Laurence G. Dyer; Bogale Tadesse (Crystals, 2024)
Alkaline EDTA solution has been previously identified as an effective leaching agent for solubilising rare-earth oxalates. These oxalates are the product of an oxalic acid conversion leach dissolving monazite and redepositing the salt. Pervious work suggested a significant increase in recovery was observed between pH 8 and 10; we have demonstrated that, in an excess of EDTA, this is not the case, and the dissolution is similar. While demonstrating that, at a nominal solid loading of 100 g/L, 0.2 M EDTA solution produced the highest dissolution, elevated solids require an equivalent increase in lixiviant concentration driven by consumption. Very-high-solution concentrations (>50 g/L dissolved TREEs) were achieved at a high solid loading, indicating both that a solution equilibrium is yet to be reached and that a build-up of oxalate in the system (estimated at ~1 M) does not impact the leach efficiency. We have also demonstrated the recycling of EDTA to use in multiple stages as well as the ability to recover oxalate from this solution.